Assessment of viral community functional potential from viral metagenomes may be hampered by contamination with cellular sequences. Issue 12 (December 2013) - Roux, Simon; Krupovic, Mart; Debroas, Didier; Forterre, Patrick; Enault, François
Abstract : Although the importance of viruses in natural ecosystems is widely acknowledged, the functional potential of viral communities is yet to be determined. Viral genomes are traditionally believed to carry only those genes that are directly pertinent to the viral life cycle, though this view was challenged by the discovery of metabolism genes in several phage genomes. Metagenomic approaches extended these analyses to a community scale, and several studies concluded that microbial and viral communities encompass similar functional potentials. However, these conclusions could originate from the presence of cellular DNA within viral metagenomes. We developed a computational method to estimate the proportion and origin of cellular sequences in a set of 67 published viromes. A quarter of the datasets were found to contain a substantial amount of sequences originating from cellular genomes. When considering only viromes with no cellular DNA detected, the functional potential of viral and microbial communities was found to be fundamentally different—a conclusion more consistent with the actual picture drawn from known viruses. Yet a significant number of cellular metabolism genes was still retrieved in these viromes, suggesting that the presence of auxiliary genes involved in various metabolic pathways within viral genomes is a general trend in the virosphere.